Self-narrative reconstruction in emotion-focused therapy: A preliminary task analysis - Cunha, Carla Alexandra Castro (2017)
Objective: This research explored the consolidation phase of emotion-focused therapy (EFT) for depression and studies—through a task-analysis method—how client–therapist dyads evolved from the exploration of the problem to self-narrative reconstruction. Method: Innovative moments (IMs) were used to situate the process of self-narrative reconstruction within sessions, particularly through reconceptualization and performing change IMs. We contrasted the observation of these occurrences with a rational model of self-narrative reconstruction, previously built. Results: This study presents the rational model and the revised rational-empirical model of the self-narrative reconstruction task in three EFT dyads, suggesting nine steps necessary for task resolution: (1) Explicit recognition of differences in the present and steps in the path of change; (2) Development of a meta-perspective contrast between present self and past self; (3) Amplification of contrast in the self; (4) A positive appreciation of changes is conveyed; (5) Occurrence of feelings of empowerment, competence, and mastery; (6) Reference to difficulties still present; (7) Emphasis on the loss of centrality of the problem; (8) Perception of change as a gradual, developing process; and (9) Reference to projects, experiences of change, or elaboration of new plans. Conclusions: Central aspects of therapist activity in facilitating the client's progression along these nine steps are also elaborated